HISTORY OF ISLAMIC CIVILIZATION AND THOUGHT IN INDONESIA (Adnin International Multidiciplinary Journal, 2025)
This article discusses the historical dynamics of the entry of Islam into Indonesia, the process of Islamization, and the development of Islamic civilization and thought from the classical period to the contemporary era. Islam entered the archipelago through various channels such as trade, marriage, education, Sufism, art, da'wah, and politics, which took place peacefully and adaptively to local culture. Islamic civilization developed in various fields, including education, economy, politics, building art, and customs and culture. This article also reviews the development of classical Islamic thought rooted in Sufism and traditional Islamic boarding schools, to modern and contemporary thought that emphasizes rationality, democracy, pluralism, and social justice. Figures such as Hamzah Fansuri, Haji Agus Salim, Nurcholish Madjid, and Azyumardi Azra play an important role in shaping the inclusive and moderate face of Indonesian Islam. By integrating local and global values, Indonesian Islam is now a unique and relevant Islamic model in facing the challenges of the times.